Factors Affecting the Use of Contraceptive in Indonesia: Analysis from the National Socioeconomic Survey (Susenas) - Idris, Haerawati (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Rapid population growth has become a major concern and attention of many national governments and international community. Most developing countries have acknowledged the role of family planning as an effective way to improve maternal/child health and suppress population growth. This study aimed to investigate the socioeconomic and demographic factors that influence the use of contraceptives in Indonesia. This was a cross-sectional study using secondary data derived from National Socio-Economic Survey (SUSENAS) in 2014. A sample of 286,695 married women was selected for this study. Multiple logistic regression analyses were used to estimate the effects of socio-economic and demographic variables on contraceptive use. Only 42% of married women in Indonesia used contraceptive method. The most popular contraceptive method was injection (55%). Factors affecting contraceptive use were maternal age of 30-34 year, living in the urban area, family wealth status in the 4th quintile, secondary school, working women, residing in Java/Bali, and the number of living children > 2. Family planning policy information, education, and communication program should consider these determinants of contraceptive use.